2010
DOI: 10.1007/s10096-010-0975-2
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory infection due to Mycoplasma pneumoniae: current status of diagnostic methods

Abstract: Because of the absence of well-standardized both in-house and FDA-approved commercially available diagnostic tests, the reliable diagnosis of respiratory infection due to Mycoplasma pneumoniae remains difficult. In addition, no formal external quality assessment schemes which would allow to conclude about the performance of M. pneumoniae diagnostic tests exist. In this review, the current state of knowledge of M. pneumoniae-associated respiratory infections in the context of epidemiological studies published d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
12

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 91 publications
1
72
0
12
Order By: Relevance
“…Sensitivities of serologic assays for the detection of Mycoplasma pneumoniae antibodies are known to vary (Beersma et al, 2005;Loens et al, 2010), IgM ELISA used in our previous study was found to be the most sensitive and specific (Abdul-Wahab et al, 2013), which is in agreement with the results obtained by other studies (Waris et al, 1998;Dorigo-Zetsma et al, 1999;Souliou et al, 2007;Vervloet et al, 2007;Myeong et al, 2012), IFA assay on the other hand, was found more sensitive and specific in adults (Andreu et al, 2006), the assay is relatively easy to perform and gives quantitative results but the main limitations are subjectivity of the interpretation of results and cross-reaction with rheumatoid factor (Vervloet et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivities of serologic assays for the detection of Mycoplasma pneumoniae antibodies are known to vary (Beersma et al, 2005;Loens et al, 2010), IgM ELISA used in our previous study was found to be the most sensitive and specific (Abdul-Wahab et al, 2013), which is in agreement with the results obtained by other studies (Waris et al, 1998;Dorigo-Zetsma et al, 1999;Souliou et al, 2007;Vervloet et al, 2007;Myeong et al, 2012), IFA assay on the other hand, was found more sensitive and specific in adults (Andreu et al, 2006), the assay is relatively easy to perform and gives quantitative results but the main limitations are subjectivity of the interpretation of results and cross-reaction with rheumatoid factor (Vervloet et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Un incremento de cuatro veces o más en el título de anticuerpos indica una infección reciente. 65 El inconveniente de utilizar IgM como marcador de infección aguda en niños radica en que pacientes menores de 6 meses pueden no producir IgM. Otra importante limitación de la serología para el diagnóstico de infección aguda por M. pneumoniae radica en una inadecuada producción de anticuerpos en algunas infecciones o una respuesta inmune humoral deficiente como resultado de alguna inmunosupresión.…”
Section: B) Inmunoensayo Enzimático (Elisa)unclassified
“…66 Las muestras clínicas disponibles para la prueba de PCR incluyen secreciones orofaríngeas y nasofaríngeas, esputo, lavado traqueobronquial y biopsia de pulmón. 65 Se ha sugerido que el uso de la PCR en combinación con la serología puede proporcionar un mejor diagnóstico y puede ayudar a distinguir entre colonización e infección verdadera.…”
Section: B Detección De áCidos Nucleicosunclassified
“…A worldwide rise in the frequency of M. pneumoniae-associated lower respiratory tract disease has been observed, from 6 ->30% in the 1990s, to 0 -66.7% in 2010 [Reviewed by Loens et al, , 2010. Therefore the pathogenic role of M. pneumoniae in respiratory disease has been proved in persons of all ages, sometimes causing severe respiratory disease, and it may induce clinically significant manifestations in extrapulmonary sites by direct invasion and/or immunologic effects.…”
Section: Urogenital Tract Glucose Arginine Ureamentioning
confidence: 99%